1994
DOI: 10.1177/036354659402200218
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Injuries in Sprinters

Abstract: Eleven sprinters with recent hamstring injuries were compared with nine uninjured runners. The flexibility of the hamstrings and the eccentric and concentric muscle torque were measured in the hamstrings and quadriceps muscles at different angular velocities. Sprinters with a previous hamstring injury had significantly tighter hamstrings than uninjured sprinters had. The uninjured sprinters had significantly higher eccentric hamstring torques at all angular velocities. They also had significantly higher concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…22,26 The fibrotic process of scar formation results in tissue contraction, reduced compliance, and altered local biomechanics, all of which have been postulated to contribute to the increased risk of recurrent injury. 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…22,26 The fibrotic process of scar formation results in tissue contraction, reduced compliance, and altered local biomechanics, all of which have been postulated to contribute to the increased risk of recurrent injury. 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Jönhagen et al 41 The second, and in most cases preferable, study design is the cohort study, where all data are collected in a standardised manner prospectively in time. The approach involves measuring potential risk factors before injuries occur, after which new cases and exposure are reported during a period of follow up.…”
Section: Andmentioning
confidence: 99%
“…Muscle damage was the primary mechanism that contributed to muscle soreness and strength loss that followed eccentric exercise (Eston et al, 1995). In another study of two subject groups, one with and one without a recent hamstring injury, it was demonstrated that the injury group had a significantly tighter hamstring and a decreased range of motion when compared to the uninjured group (Jonhagen et al, 1994). One additional finding revealed that the injury group had weaker eccentric contractions and weaker concentric contractions at slower velocities.…”
Section: Introductionmentioning
confidence: 99%